What an Emerging Trump Administration Means for Lesbian, Gay, Bisexual, and Transgender Health - Gilbert Gonzales; Tara McKay (Mary Ann Liebert, 2017)
The policies of the Trump administration are likely to have direct and indirect implications for lesbian, gay, bisexual, and transgender (LGBT) health. With the assistance of a Republican-controlled Congress, President Trump may repeal President Obama's health reform law, undermine same-sex marriage laws and other nondiscrimination protections, reduce funding for research on sexual and gender minority health, and institutionalize discrimination through new legislation, such as the First Amendment Defense Act. Public health researchers, healthcare providers, and professional organizations must continue to combat discrimination and advocate for LGBT health equity under an emerging Trump presidency.